1998
DOI: 10.1111/j.1444-0938.1998.tb06735.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of a low vision clinic population

Abstract: BACKGROUND: Causes of low vision and types of low vision devices (LVDs) prescribed in other low vision clinics have been studied extensively. Similar studies have not been conducted in Malaysia. This paper reports the results of a retrospective study of 573 patients seen at the Universiti Kebangsaan Malaysia-Malaysian Association for the Blind (UKM-MAB) low vision clinic in Kuala Lumpur. METHODS: The record cards of 573 patients seen at the UKM-MAB clinic over 10 years were examined and the following informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
18
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 15 publications
14
18
6
1
Order By: Relevance
“…This depiction of ayounger population is similar to findings from Malaysia [14], Korea [6], Nepal [15], and India [16] in which theproportion of patients aged below 50 years were 74%,69%, 58% and 68% respectively. In these developingcountries, the proportion of low vision patients aged60 years and above ranged between 16% and 26%.On the other hand, in studies from developed countries,Leat and Rumney [17] (United Kingdom) found77% of their patients to be aged 60 years and above; Elliotet al [11] (Canada) reported that 66% of patientswere 70 years or older; while in Australia, Wolffsohnand Cochrane [12] observed that 87% of patients wereaged 60 years and above.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This depiction of ayounger population is similar to findings from Malaysia [14], Korea [6], Nepal [15], and India [16] in which theproportion of patients aged below 50 years were 74%,69%, 58% and 68% respectively. In these developingcountries, the proportion of low vision patients aged60 years and above ranged between 16% and 26%.On the other hand, in studies from developed countries,Leat and Rumney [17] (United Kingdom) found77% of their patients to be aged 60 years and above; Elliotet al [11] (Canada) reported that 66% of patientswere 70 years or older; while in Australia, Wolffsohnand Cochrane [12] observed that 87% of patients wereaged 60 years and above.…”
Section: Discussionsupporting
confidence: 71%
“…Thesmall sample size of our study may account for this difference.It is thus necessary to educate eyecare providers and glaucoma patients about the availableoptions of low vision assessment and low visual aids.Contrary to the previous report by Richard [23] inwhich cataract was the most common cause of low vision,cataract was not present in our study as were not included .The major causes of low vision within the different agegroups as shown in Figure 1 are quite similar to otherreports [12,14]. As expected, congenital and heritable conditionswere more common in children, while age relateddiseases were predominant in the elderly patients.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Of these, 55% of eyes were blind at six months follow up [14] . In a retrospective study of 573 patients seen at the Universiti Kebangsaan Malaysia-Malaysian Association for the Blind (UKM-MAB) low vision clinic in Kuala Lumpur, Mohidin and Yosuf [15] reported that the main causes of low vision were congenital structural defects including nystagmus among patients in the zero to 29 years age group, retinitis pigmentosa among the 30 to 59 years age group and age related macular degeneration among those over 60 years of age. Three hundred and forty one (59.5%) patients seen at the low vision clinic accepted the use of low vision devices.…”
Section: Introductionmentioning
confidence: 99%